Experimental study on the influence of pore structure on spontaneous imbibition in marine black shale - Changqing Fu; Xiang Xu; Yi Du; Xin Kou (Capillarity, 2024)
Recently, significant progress has been made in the exploration of marine shale gas in the Qiongzhusi Formation of the Sichuan Basin, China. Micro/nanopores within this formation play a crucial role in spontaneous imbibition and subsequent shale gas production. In this paper, to investigate the influence of pore structure in the Qiongzhusi shale on the spontaneous imbibition characteristics, two sets of samples with varying mineral contents were subjected to horizontal and vertical spontaneous imbibition experiments. Onedimensional transverse relaxation time, two-dimensional longitudinal-transverse relaxation time, and layer division transverse relaxation time spectra from low-field nuclear magnetic resonance were analyzed to elucidate fluid migration during spontaneous imbibition as well as contributions from different pore sizes toward the overall imbibition capacity. The results indicated that, among different pore sizes, mesopores have the greatest impact on the imbibition rate of marine carbonaceous shale, followed by micropores and macropores. The organic matter and clay minerals in carbonaceous shale were found to play a significant role in enhancing the permeability and absorption rate by the presence of abundant mesopores. Besides, the bedding development of marine carbonaceous shale in the Qiongzhusi Formation influences the imbibition process. The horizontal samples exhibited lower levels of imbibition efficiency than their vertical counterparts. Document Type: Original article Cited as: Fu, C., Xu, X., Du, Y., Kou, X. Experimental study on the influence of pore structure on spontaneous imbibition in marine black shale. Capillarity, 2024, 10(3): 57-72. https://doi.org/10.46690/capi.2024.03.01